PENGARUH LOAN TO DEPOSIT RATIO PADA PROFITABILITAS DENGAN NON PERFORMING LOAN SEBAGAI PEMODERASI - Widiasari, Ni Kadek Yuni; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2015)
Profitability is the ability of a financial institution in profit from operations in order to generate revenue for the financial institution. Some ratios that affect the profitability of LPD, including the LDR and NPL. NPL chosen as a moderating for NPL able to weaken or strengthen the effect of LDR with profitability. The purpose of the study to determine the effect of variables on the profitability of the NPL LDR as a moderating variable. This research was conducted at the LPD Tabanan 2012-2013. The sampling method used purposive sampling with a sample of 44 LPD and analysis techniques used are Simple Linear Regression and Moderated Regression Analysis (MRA). The results showed that LDR partially positive effect on profitability while NPL negatively affect the relationship between the LDR with profitability. This proves that an increase in the performance of rescue troubled loans made ??by LPD in Tabanan as indicated by the relatively small value of NPLs that did not significantly affect the profitability of
Keywords: LDR, ROE, Profitabilitas, NPL